Pengaruh Politik Lokal Pada Pemilihan Kepala Daerah - Paiman Eliaezer Nadeak; Zito Yonatan Sinaga; Jessica Evi Margaretha Simanjuntak; Julia Ivanna (Public Service and Governance Journal, 2022)
The implementation of direct pilkada was not without problems. The regional head elections which have been held so far have had quite a lot of internal challenges. This research is qualitative research, the determination of informants purposively is also based on subjective reasons which have limited funds, time in conducting this research. The research results show that generally the elite and the public already know that the election Regional Heads and Deputy Regional Heads will be elected directly by the community. There must be in-depth socialization from the government, in this case the KPUD regarding the implementation of the Pilkada as well as the role of elites and existing political parties.